Efektivitas Model Contextual Teaching And Learning Berbantuan Media Word Search Terhadap Maharah Qira’ah - Mita Eliza; Yuniar Yuniar; Kemas Muhammad (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
The low level of students' Arabic reading skills is often caused by monotonous learning methods and a lack of initial vocabulary mastery, which leads to difficulties in comprehending texts as a whole. This issue is reinforced by field facts showing that the students' initial average scores remain below the minimum mastery standard. This study aims to examine the effectiveness of the Contextual Teaching and Learning model assisted by Word Search media in improving Maharah Qira’ah. Using a mixed-method approach, the research involved 52 ninth-grade students at SMP Azharyah Palembang. Data were collected through observation, interviews, tests, and student response questionnaires, with data analysis conducted using the Independent Sample t-Test. Quantitative analysis results showed a significant increase in the experimental class with a post-test average of 77.60, exceeding the control class at 64.44, with a Sig. (2-tailed) value of 0.006 < 0.05. This study is supported by highly positive student responses, with the average motivation reaching 93.23%. Qualitatively, observations indicated that students became more active and enthusiastic about discovering textual meanings independently. The novelty of this research lies in the integration of Word Search media as scaffolding within the contextual learning framework, which facilitates interactive vocabulary identification. This innovation is effective as a bridge for students before engaging in more complex reading comprehension tasks.